Criminal Responsibility For Embezzlement Of Hajj and Umrah Pilgrimage Funds - Widodo, Widodo; Maryono, Maryono; Hansanontha , Pataree (CV. Era Digital Nusantara, 2024)
This study aims to analyse the criminal liability of the perpetrators of embezzlement of Hajj and Umrah funds in the Indonesian criminal justice system and evaluate the effectiveness of legal sanctions applied to tackle these criminal acts. This research uses a normative juridical method with a descriptive qualitative approach, which focuses on analysing the laws and regulations and their application in cases of embezzlement of Hajj and Umrah funds. The results show that although there are clear regulations related to the embezzlement of Hajj and Umrah funds, law enforcement is still hampered by various factors, such as the lack of supervision of worship trip organisers and the less-than-optimal sanctions applied. This research suggests the need to strengthen supervision, increase the capacity of law enforcers, enforce firmer sanctions, and improve the regulation of Hajj and Umrah fund management. Thus, this study contributes to the improvement of the legal system and management of Hajj and Umrah funds in Indonesia.